The Reflection of Online Education during the Covid-19 Pandemic on Nursing Students' Care Behaviors and Stress - Aydanur Aydin (Journal of Education in Science, Environment and Health)
The pandemic period creates a feeling of inadequacy in applying the education that students receive. During this period, students who receive online education seem to feel inadequate and experience stress in a practical lesson. It aims to evaluate the level of changing the care behaviors of undergraduate nursing students and the stress they experience during the Covid-19 process. This research was completed with a nursing student in 2192 in Turkey. The research is descriptive and relationship-seeking. Data were collected at the end of the semester with the caring behaviors competency and the stress scale. t-tests, Kolmogorov-Smirnov tests, and correlation tests were used in the analysis of the data. Bachelor of Science in Nursing (BSN) students are predominantly in the first year of study. A significant difference was found in the perceived stress level according to the variables of gender, education level, perceived care sufficiency, and the type of university attended. It was determined that the caring behaviors of male students were higher than females, and those in private schools were higher than those in public universities. Nursing students' age, class, and perceived stress scores significantly affect their care behavior. Nursing education in Turkey focuses on care-based education which emphasizes skill development across the BSN program, establishing measurable care behavior, and ensuring that managing student stress is part of the curriculum content.